Characterization of Surface Runoff Pathways and Erosion Using Hydrological Attributes Under Simulated Rainfall - Zhang, Lichao; Liu, Xiaojun; Song, Yuejun; Li, Jun; Cai, Chongfa; Zhao, Xiaomin; Li, Zhaoxia (Frontiers in Earth Science, 2021)
Conceptualisation of geo-hydrological characteristic of erosive runoff are of particular importance and has been required in recent soil erosion control. This study aimed to explore the feasibility of applying hydrological attributes to characterize surface runoff pathways in the process of hillslope soil erosion due to rainfall. Combined with sub-millimeter high-resolution laser scanning and computer digital image processing method, three hydrological indicators (i.e., sinuosity, gradient and orientation) were used to investigate the changes of the surface runoff pathways on the slope of three typical southern red soils (i.e., shale (HS), and Quaternary red clay soils (HQ1 and HQ2) under simulated rainfall conditions). The results indicated no significant changes of sinuosity with a mean value of 1.19. After the rainfall with the intensity of 1 mm/min and 2 mm/min, the orientation and gradient changed dramatically. The greatest changes appeared at the first rainfall, which showed that the biggest increase of gradient was 26.78% and it tended to be close to the original slope of the test plot, while the orientation dropped by 5.60–31.44%. Compared with HS and HQ1, the runoff pathway characteristics of HQ2 changed more consistent. The rainfall intensities had a significant impact on the correlation between indicators. The determination coefficients sorting with surface roughness were orientation > graient > sinuosity. And they were significantly linearly related to runoff under 1 mm/min rainfall intensity, while had positive correlation with sediment under 2 mm/min rainfall intensity (p < 0.05). In conclusion, there were more remarkable relationships between orientation, gradient and slope erosion under 1 mm/min rainfall intensity. This provided an innovative idea, that is applying the orientation and gradient to the simulation and prediction model of the rainfall erosion process in the sloping farmland in the southern red soil area.